Caffeine reduces accuracy in face recognition memory consolidation - León, Candela Sofía (2025)
Numerous studies have shown that caffeine facilitates cognition, particularly memory, when consumed before learning and immediately tested. However, most of this evidence relates to its effects during encoding, and the role in memory consolidation remains unclear. A key study demonstrated that caffeine administered after learning can enhance object recognition memory consolidation by improving discrimination between previously seen targets and similar lures. Here, we investigated the effects of post encoding caffeine on the consolidation of face recognition memory using a randomized, double-blind design. Participants (N = 97) viewed ten generated faces on Day 1 and then received 200 mg of caffeine or placebo. On Day 2, they completed a recognition task under two conditions: Present condition (original face with five similar distractors) or Absent condition (six similar distractors) adding a “none of the above” option. The results showed that, contrary to our expectation, caffeine consumption did not improve the consolidation of face recognition memory. Instead, we observed a general impairment in recognition performance, suggesting a reduced ability to distinguish previously encountered from novel but similar faces. These findings discuss the idea of caffeine as a general cognition enhancer and aligned with studies suggesting it enhances global processing at the expense of detailed discrimination.